Diversity studies in groundnut (Arachis hypogaea L.) genotypes: DIVERSITY STUDIES IN GROUNDNUT GENOTYPES - N RAMYA SELVI; P L VISWANATHAN; S MANONMANI (Journal of Oilseeds Research, 2020)
An experiment was conducted to assess the diversity that exists among seventy-five genotypes (COG 17001 to COG 17075) with five checks [CO7, VRI 8, TMV (Gn) 13, TMV 14 and ICGV 07222] of groundnut. Observations recorded for seventeen agronomic traits were subjected to Mahalanobis D2 analysis. Statistical analysis revealed that maximum diversity between the genotypes was contributed by kernel yield per plant (g). Variability contributed by this trait in PCA had high factor loading (0.0382). The principal component analysis indicated that, the first six principal components had Eigen value more than one and exhibited 76.98% of maximum variability among eighty genotypes for seventeen characters.